Impact of mode of delivery on pregnancy outcomes in women with premature rupture of membranes after 28 weeks of gestation in a low-resource setting: A prospective cohort study - Kayiga, Herbert; Lester, Felicia; Amuge, Pauline M.; Byamugisha, Josaphat; Autry, Amy M. (PLoS ONE, 2018)
Despite the high prevalence of premature rupture of membranes (PROM) in low-resource settings, the preferred mode of delivery remains unclear. We compared the perinatal mortality in a prospective cohort of women with PROM after 28 weeks following vaginal or caesarean delivery at Mulago Hospital with the aim of adopting evidence based practice and improving patient care. Methods Between November 2015 and May 2016, 1455 women with PROM after 28 weeks of gestation and their newborns were prospectively followed from admission to discharge at Mulago Hospital. The primary outcome was perinatal mortality. Secondary neonatal outcomes included sepsis and admission to the Special Care Unit. Maternal outcomes included maternal deaths and complications. Outcomes were compared between women who had vaginal vs. caesarean delivery using multivariable logistic regression. All statistical tests were 2-sided with the level of statistical significance set at p < 0.05. Results The incidence of PROM was 12.1%. The perinatal mortality following PROM was 65 per 1000 live births. Of the 1425 women with PROM, 991 (69.5%) had vaginal delivery and 434 (30.5%) underwent Caesarean section. There was no statistical difference in perinatal mortality by the mode of delivery (vaginal vs. caesarean) in PROM (p = 0.12). The risk factors for perinatal mortality included chorioamnionitis, failure to administer corticosteroids in preterm PROM, gestational age (28–33 weeks), duration of drainage of liquor (24–48 hours), and presence of maternal complications. Caesarean delivery was associated with increased maternal postpartum infections, admission to the Special Care Unit and maternal death. Conclusion In low resource settings, vaginal delivery is the preferred mode of delivery for PROM after 28 weeks gestation. It is associated with lesser maternal and perinatal morbidity when compared to caesarean delivery.